KUAT TEKAN BETON MUTU TINGGI HYBRID DENGAN SUBSTITUSI SEMEN DAN AGREGAT HALUS SERTA PENAMBAHAN NANO MATERIAL BIJIH BESI - Nora Usrina; Teuku Budi Aulia; Muttaqin Muttaqin (Prodi Magister Teknik Sipil Unsyiah, 2018)
SNI 03-6468-2000 defines a high-quality concrete as a concrete with a compressive strength equal to or larger than 41,4 MPa. To obtain a high strength concrete, increasing the quality of material components is needed. The improvement of concrete quality can be done by addition or substitution processes in the concrete mixture. In this research, the substitution of cement, fine aggregate and coarse aggregate with fly ash coal, palm shells, pozzolan sands and the addition of iron ore nanomaterial as filler (BMT-H) were selected. The purpose of this research is to compare the compressive strength of hybrid high-quality concrete (BMT-H) to normal high-quality concrete (BMT-N). Samples of concrete compressive in a cylindrical shape with diameter 15 cm and height 30 cm were prepared. Concrete compressive strength test was performed on concrete at age of 7 days, 28 days, and 56 days. The results of compressive strength maximum on concrete at age 7 days, 28 days and 56 days are 44,28 MPa; 59,48 MPa and 69,71 MPa, consecutively.